2021
DOI: 10.14740/jmc3639
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Air Embolism After Gastrointestinal Procedure: A Case Report and Literature Review

Abstract: Esophagogastroduodenoscopy (EGD) is one of the forefronts of minimally invasive modalities with excellent safety records and tremendous capability but despite its accolades and functions, there are still very rare complications including air embolism. It is a life-threatening condition that could lead to a significant increase in morbidity and mortality. However, there are limited data for incidence of air embolism in association with gastrointestinal endoscopy. Diagnosis of air embolism after or during gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 6 , 7 In total there appear to be only 13 reported cases of CAE after EGD, reinforcing its rarity. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 In total there appear to be only 13 reported cases of CAE after EGD, reinforcing its rarity. 8 …”
Section: Discussionmentioning
confidence: 99%
“…6,7 In total there appear to be only 13 reported cases of CAE after EGD, reinforcing its rarity. 8 There are a variety of proposed mechanisms by which gas can enter vasculature during endoscopy including through the portal vein, exposed gastrointestinal vessels, or through adjacent veins of inflamed mucosa. 2 Theories on how air reaches the arterial system, and specifically the central nervous system, include paradoxical embolization through heart shunts such as a patent foramen ovale, retrograde flow through the superior vena cava, and through pulmonary veins if not filtered by the pulmonary system.…”
Section: Discussionmentioning
confidence: 99%
“…Air may enter directly through exposed vessels within gastric ulcers or gastric tumors. The higher-pressure gradients secondary to the insufflation of air during the procedure are further hypothesized to facilitate air entry [ 5 , 6 ]. Translocation of air from the venous circulation to the systemic circulation can be secondary to intracardiac shunts like PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that early identification and early initiation of HBO therapy result in improved outcomes in CAE patients. HBO is believed to help by decreasing the size of gas emboli and providing higher oxygen concentrations in arterial blood which may benefit the ischemic tissue [ 1 , 2 , 4 , 6 ]. Initiating HBO therapy more than six hours after insult, as well as early and significant ischemic changes seen on CT/MRI before starting therapy were both considered strong predictors of poor neurological and clinical outcomes [ 1 , 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation